2014
DOI: 10.1371/journal.pone.0106079
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence, Sources and Spatial Characteristics of Soil Salt and Assessment of Soil Salinization Risk in Yanqi Basin, Northwest China

Abstract: In order to evaluate the soil salinization risk of the oases in arid land of northwest China, we chose a typical oasis-the Yanqi basin as the research area. Then, we collected soil samples from the area and made comprehensive assessment for soil salinization risk in this area. The result showed that: (1) In all soil samples, high variation was found for the amount of Ca2+ and K+, while the other soil salt properties had moderate levels of variation. (2) The land use types and the soil parent material had a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Climate, terrain features and groundwater table also cause soil salinization. Then, human activity aggravates soil salinization to different levels [27][28][29]. Soil salinization has obvious seasonal characteristics, as dramatic increase in evaporation (due to high spring temperatures) results in salt deposition.…”
Section: Changes In Cultivated Landsmentioning
confidence: 99%
“…Climate, terrain features and groundwater table also cause soil salinization. Then, human activity aggravates soil salinization to different levels [27][28][29]. Soil salinization has obvious seasonal characteristics, as dramatic increase in evaporation (due to high spring temperatures) results in salt deposition.…”
Section: Changes In Cultivated Landsmentioning
confidence: 99%
“…China is one of the largest cotton producing and cotton consuming countries in the world [1]. Currently, Xinjiang province is the largest cotton producing area in China [4]. Unfortunately, until now, although soil salt-alkalization could lead to crop growth damage and a decrease in crop yields, little attention has been paid on the molecular mechanisms of plant adaptation to alkaline stress [7].…”
Section: Resultsmentioning
confidence: 99%
“…Corwin and Lesch (2005) reported moderate to high variability in EC e in salinesodic soil. Zhaoyong et al, (2014) observed moderate variability in EC e while assessing the soil salinization risk in Yanqi basin, northwest China. Electrical conductivity is an important diagnostic parameter for evaluation of soil salinity.…”
Section: Electrical Conductivity (Ec E ) Of Saturation Extractmentioning
confidence: 88%